Impact of Watson's human caring-based health promotion program on caregivers of individuals with schizophrenia - Shahpar Bagheri; Ladan Zarshenas; Mahnaz Rakhshan; Farkhondeh Sharif; Ebrahim Moghimi Sarani; Zahra Hadian Shirazi; Kathleen Sitzman (BMC, 2023)
Abstract Background Caring for people with schizophrenia is accompanied by challenges that impact caregiver health. We conducted this study to explore the effect of a Caring Science-Based health promotion program on the sense of coherence and well-being among caregivers of persons with schizophrenia. Methods This randomized clinical trial with the Solomon four-group design was conducted on 72 caregivers randomly allocated into two intervention and two control groups. A health promotion program based on Watson's theory was performed individually through five face-to-face sessions and a four-week follow-up. Settings were the psychiatric centers of the three educational, specialty, and subspecialty Ibn-e-Sina, Moharary, and Hafez hospitals affiliated with Shiraz University of Medical Sciences (SUMS), south of Iran. The data were collected using a demographic information form, the Sense of Coherence Scale, and the Caregiver Well-Being Scale. One-way ANOVA, chi-square, Kruskal-Wallis, and independent t-test were used to determine the homogeneity at baseline. In the post-test, multiple between-groups and pairwise comparisons were assessed by One-way ANOVA and Tukey's post-hoc. Within-group comparisons were evaluated using paired t-tests. All tests were two-tailed, and the statistical level was considered 0.05. Results Data analysis showed that the mean scores of caregiver sense of coherence and well-being from pre-intervention to post-intervention were significantly increased in the intervention groups (p < 0.001). At the same time, there were no significant differences in the control groups. Conclusion The health promotion program based on Watson's human caring theory facilitated ongoing intrapersonal, and holistic caring and improved the sense of coherence and well-being in caregivers of persons with schizophrenia. Hence, this intervention is recommended for developing healing care programs. Trial registration https://www.irct.ir/trial/55040 : IRCT20111105008011N2 (11/04/2021).